(untitled) (Journal of Mathematical Study, 2022)
In this paper, we establish the boundedness of the bilinear fractional integral operator B_α and the subbilinear fractional maximal operator M_α on vanishing generalized Morrey spaces V_0L^p,φ(R^n), V_∞L^p,φ(R^n) and V^(*)L^p,φ(R^n). The main novelty of this article is that we control B_α by the subbilinear maximal operator M and M_α' with α'>α. Some specific examples for the main results of this paper are also included.